Stubble Height Impact on Forage Accumulation and Nutritive Values in Native Meadows - Junior Issamu Yasuoka; Wendie Powell; Bruno Carneiro e Pedreira (Scientific Electronic Archives, 2024)
Forage from native prairie meadows is an important feed source in Eastern Kansas to address the challenges of shallow, acidic, and nutrient-poor soils. However, it is crucial to establish an optimal stubble height to optimize forage accumulation (FA) and nutritive value (NV). Our objective was to evaluate the impact of stubble height on FA and NV in native prairie meadows in Eastern Kansas. The study was conducted in native meadows using a randomized complete block with three replications across three locations (Parsons, Caney, and Coyville, all located in Eastern Kansas). Treatments were four stubble heights (2.5, 7.5, 12.5, and 17.5 cm). Shorter stubble height resulted in greater FA, as it removes a greater proportion of the forage accumulated. Forage accumulation was slightly higher when harvested at 7.5- than at 12.5-cm stubble height. Crude protein content increased from 2.5- to 17.5-cm stubble height with no differences between 7.5- to 12.5-cm stubble height. The opposite pattern of CP occurred for CPA (Table 3), with only 25 kg in difference from 7.5- to 12.5-cm stubble height. Stubble height did not affect fiber content (NDF and ADF) and energy content (TDN, NEL, NEG, and NEM). Thus, stubble height from 7.5 to 12.5 cm provides great FA and CPA in native prairie meadows. However, to ensure long stand life and better CP content, stubble height above 12.5 cm should be preferred, which may contribute to reducing animal supplementation costs.